Architectural and Historical Qualities of Kalkan as an Authentic Settlement - Karabağ, Kutay (YILDIZ TECHNICAL UNIV, 2018)
As the only sheltered bay between Fethiye and Kas, Kalkan have connected fertile Esen Plain and high plateaus on both sides of Akdaglar, with the abroad locations. Although the water supply and the commercial potential of the coast had been utilized throughout the history, the settlement sprouts at the beginning of the 19th century and evolves into a lively port town in the second half. To use the old name,'Kalamaki', was an Ottoman 'nahiye' with Greek majority until the population exchange in 1924, and the liveliness had lasted until 1950s. The port had functioned for the transfer of agriculture and forest products to various Mediterranean ports, as well as distribution of imported industrial products throughout the hinterland. These trade connections had brought a continous cultural exchange, which is also eminent in the local fabric and architectural features, as a function of various cultures and local factors. Building islands are usually composed of a few adjacent blocks in order to avoid hindering the view and the breeze, while the space in-between operates as street. In general, buildings are simple rectangular stone blocks oft stories nestled on the slope. Whilst plot borders correspond to the building borders in small examples, larger buidings utilize other types of open spaces such as garden and courtyard. Although, the town is under conservation and still possess a level of authenticity, Kalkan turned into a tourism town in 1980s, and particularly around 2000 intensification of uncontrolled growth have begun to threaten the overall integrity of the settlement. This article aims to present the architectural and urban qualities of the traditional fabric regarding historical, geographical and social factors shaping it. In the final part, author discusses the authenticity of the architectural and urban features of the fabric followed with some proposals.
Keywords: Traditional fabric; Kalkan; Kalamaki; conservation; tourism; vernacular architecture